Pemanfaatan Aplikasi Facebook Dalam Membangun E-Learning Dengan Metode Asynchronous Collaborative Learning di Politeknik Cilacap - Gusti Darma Yudha (Esensi: Jurnal Bisnis dan Manajemen, 2014)
The development of information systems in human life along with the of human civilization itself until finally getting to know the term information technology. Pay attention to the development of such information, we will study briefly the history of information technology in an effort to get the integrity of science and knowledge about information technology. History of technology we can divide into pre-history, past history, and modern times. The utilization of ICT in learning in Indonesia has had a long enough history. Initiative hosted the radio broadcast education and educational television is an attempt do the dissemination of information to the education units are scattered throughout the archipelago. This is a manifestation of consciousness to optimize the domestication of technology in helping the learning process of the community. Along with the need for methods and concept learning is more effective and efficient, the utilization of information technology for education was not inevitable. The concept would later be known as e-learning brings the influence of conventional education, to the process of tranformasi in digital form, either generally contents (contents) and his system. This research aims to apply and implement the concept of e-learning is a teaching and learning that enables tersampaikannya learning materials to students using internet media. With the e-learning is expected to facilitate the teaching and learning process is conducted without limited location, time and costs. The method is done by charging a questionnaire to find out the needs of the user that there is a facebook application and utilization in building E-learning applications. The programming is done with the PHP language and customize with FBML is a framework from Facebook itself. Research results is a system application that will be used in assisting the process of teaching and learning online. This application can support distance learning. This application runs in the facebook application that is very easy to be accessed by the user, which the user is a student and lecturerDOI: 10.15408/ess.v4i3.2437